Strategies for the detection of endocrine disrupting compounds utilising recombinant oestrogen receptor ligand-binding domains and high specificity monoclonal antibodies - Tait, Timo (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.